Promoting the use of metacognitive and vocabulary learning strategies in 8th graders - Alvarez-Ayure, Claudia Patricia; Barón-Peña, Cristina; Martínez Orjuela, Magda Liliana (Íkala, Revista de Lenguaje y Cultura, 2018)
This paper reports on the results of a strategy training experience on a group of 30 A1-eight graders from two public schools in Colombia. Our goal was to identify how the development of metacognitive and vocabulary learning strategies, executed through a WebQuest, influenced the students’ performance in a vocabulary-learning task and their levels of learning autonomy. Data were analysed following the grounded theory approach. The results showed increases in the percentage of students using learning strategies, the adoption of metacognitive behaviours and levels of learner autonomy. Therefore, we propose that classroom practices should incorporate a greater degree of strategy training, mediated by Web-based tools, to help students achieve higher levels of learning control and to develop skills that can be transferred to other learning situations.